Kangaroo Mother Care (KMC) Support in Low Birth Weight (LBW ) - Noviana, Rita; Kartini, Farida (Fakultas Kedokteran, 2022)
Introduction: Kangaroo Mother Care (KMC) method is effective for Low Birth Weight (LBW). A cost-effective, evidence-based intervention that is useful for preventing or reducing complications and reducing neonatal mortality in preterm birth and low birth weight (LBW). Method: The design in study is a Scoping review, published in English, published in Indonesian, last 5 years (2017 to 2021) the database used by PubMed, Wiley online library, Science Direct, and search Google Scholar Article selection using Prism Flowchart and critical appraisal using Mixed Methods Appraisal Tool (MMAT) potential journals are exported to the Medley reference management software. Results: based on database search obtained 10 articles related to the research objectives. This research comes from countries in Asia, India, Pakistan, East Africa. It consists of qualitative, quantitative, RCT studies. There are 4 themes from the database mapping results, namely forms of KMC support. Conclusion: training and information about KMC are very necessary for mothers of low birth weigth so that mothers can do the KMC. Family support is needed to increase the desire of mothers of low birth weight to perform KMC.